2007
DOI: 10.3368/er.25.3.183
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Impacts of Restoration on Small Mammals in a Mixed-grass Colorado Prairie

Abstract: Small mammals in restored and native grassland plots were monitored at Rocky Mountain Arsenal National Wildlife Refuge in Colorado from 1997 to 2005 in order to measure the effects of restoration on small mammal communities. Variation in small mammal metrics (total captures, total biomass, and species richness) were related to both restoration efforts and interannual variation in weather. We compared remnant native grassland sites with restored grasslands and found that restoration plots experienced declines i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
3
10
0
1
Order By: Relevance
“…Despite the fact that these grasslands are about 175 km south of the historic prairie peninsula, they have been colonized by a large number of native grassland birds, including Henslow's Sparrows (Ammodramus henslowii), Dickcissels (Spiza americana), Bobwhite Quail (Colinus virginianus), Northern Harriers (Circus cyaneus), and Short-eared Owls (Asio flammeus) [6][7][8]. Prairie restorations have also been shown to support increases in grassland-dependent small mammal numbers [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that these grasslands are about 175 km south of the historic prairie peninsula, they have been colonized by a large number of native grassland birds, including Henslow's Sparrows (Ammodramus henslowii), Dickcissels (Spiza americana), Bobwhite Quail (Colinus virginianus), Northern Harriers (Circus cyaneus), and Short-eared Owls (Asio flammeus) [6][7][8]. Prairie restorations have also been shown to support increases in grassland-dependent small mammal numbers [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of grassland restoration on small 87 mammals has been addressed in a handful of studies in North America. Stone (2007) found that 88 restoration led to a short-term decline in the number of captures, total biomass and species richness 89 of small mammals, followed by a partial recovery 3-5 years after restoration. A comparison of a 90 successional gradient from prairie to forest (Moro and Gadal, 2007) showed that time since 91 restoration (abandonment) did not directly affect small mammals and that their abundance was 92 highest in middle, rather than early or late, successional stages, where the structural diversity of 93 vegetation was highest.…”
mentioning
confidence: 99%
“…Past human activities could have benefited the small mammals by reducing densities of small‐ and medium‐sized predators (such as mongoose, snakes, and birds of prey) (Caro ). The biomass, density, and diversity of small herbivores have been reported to decrease as a consequence of restoration actions (Briani et al ; Stone ). Before people moved out and restoration began, forests were degraded and it is plausible that there were few medium‐sized predators feeding on small herbivores.…”
Section: Discussionmentioning
confidence: 88%